Transformers : dark of the moon [videorecording (Blu-Ray)] - LaBeouf, Shia, 1986-; Duhamel, Josh, 1972-; Turturro, John, 1957-; Murphy, Don, 1962-; Kruger, Ehren, 1972-; Bay, Michael, 1964- (Paramount Home Entertainment, 2011)
Years after the landing on the moon, scientists struggle to understand the technology that was found on a ship that had crashed on the far side of the moon, but the Decepticons and Autobots know exactly what the technology does and it is just a matter of who gets to it first.